GPR Application for Non-Rigid Road Pavement Condition Assessment - Batrakov, Dmitry O.; Antyufeyeva, Mariya S.; Batrakova, Angelika G. (Electrical, Control and Communication Engineering, 2022)
The main aim of the article is to demonstrate the effectiveness of the use of ground penetrating radars to assess various objects using the example of assessing the current state of highways. The article uses the software developed by the authors and the corresponding mathematical models. The analysis of the results obtained is based on mathematical models that have proven their effectiveness and is time-tested. It should be emphasised that the main problem in assessing roads with non-rigid pavement is associated with a change in the main parameters of the layers – thickness and dielectric constant. Previously, we proposed a scheme for the layer-by-layer determination of the values of the relative permittivity and then - the subsequent determination of the thickness of each layer, starting from the top layer and ending with the base. The paper presents the results of experiments actually carried out by the authors with various GPRs, which not only have different values of the central frequency, but also have significant design differences. In addition, the results of processing real data using the software developed by the authors are presented. As a result, an improved method of signal calibration has been proposed, which makes it possible to increase the reliability of assessing the thickness of road surfaces, as well as other objects.